The Use of Social Media Data In Studying Leadership In Sustainable Investing A Global Phenomenon - Natali Hasto Kristijono; Hendrawan Supratikno; Rudy Pramono; Niko Sudibjo (Ridwan Institute, 2021)
This study describes a proposed alternative method to qualitatively study global phenomena which create challenges to access informants due to either geographical or time availability constraints. A mix between the capturing and usage of secondary data obtained from the abundance of social media data, an established hermeneutic phenomenology method and triangulation with conventional method is proposed. A sample case on studying leadership in sustainable investing is featured to demonstrate the application of the method. Reasons for decision to invest through the SI strategy emerge from leaders’ insight obtained from the hermeneutic circles and were supported by direct interviews. There are four reasons for decision i.e., (1) climate change, (2) stakeholders’ demand alignment, (3) risk – performance consideration, and (4) value alignment. While other characteristics of transformation leadership is intellectual stimulation represents major finding from the data. The abundance of insights on the internet, along with established qualitative research methods, computer software, as well as accessible primary source represent opportunities to replicate the example to cover other topics.